Problems and Tasks of Higher Pedagogical Education at the Present Stage of Country’s Development - G. A. Bordovsky (Высшее образование в России)
The analysis of the reasons why numerous attempts to update the Russian education system do not lead to the desired result and cause increasing criticism is carried out. One of the main reasons is seen in the violation of the systematic approach in solving the issues of the development of education in modern conditions. It is pointed out that the educational sphere, in fact, is always based on solving three problems: “what to teach”, “how to teach”, “why to teach”.The key question, that illuminates everything else, is the main question – in what social, economic and technological structure of society a person who receives education at any level, from preschool to university, has to live and work. Violation of the sequence of solving these problems, their inconsistency and the lack of a scientific justification ahead of the decisions made, inevitably lead to internal contradictions in the system being built and reduce its effectiveness.The analysis of why the Bologna system, which is widespread in a large number of countries with different levels of socio-economic status, turned out to be ineffective in Russia was made. It is shown that this system in its origin is a system of general higher non-professional education and an attempt to adapt it for receiving professional education in our country cannot be successful by its definition. It is said about the need of building a domestic multi-level system of professional higher education in modern conditions.